Epenthetic prefixation in Alawa and Marra. Issue 3 (2nd July 2020) - Harvey, Mark; Baker, Brett
ABSTRACT: Languages adopt a number of strategies to avoid dispreferred phonotactic structures. The general pattern is that such strategies involve minimum departure from the input form. One of these strategies is epenthesis. With epenthesis, the minimum departure from the input form is usually the addition of a singleton consonant or a singleton vowel. We show that Alawa and Marra have epenthetic CV syllables in prefix complexes, and that this epenthesis of a syllable is not motivated in phonological theory. We provide evidence that these prefixal structures did not originate in epenthesis, but rather were by-products of reduction processes targeting prefixed article paradigms. We propose that the synchronically epenthetic prefixes are remnants of old article roots.